The first case study of a thunderstorm in South Africa based on dual- Doppler radar observations - Gomes, A. M.; Held, G. (My University, 1992)
On 27 March 1991, an isolated thunderstorm passed between the two CSIR Doppler radars, spaced about 45km apart. Both radars simultaneously recorded Doppler data of the storm, and a detailed case study during an 11-min period is presented. Air motions synthesized from these data provide the first three-dimensional display of Doppler-derived wind fields within a multicell storm on the Transvaal Highveld. Regions of high divergence values (10 -2s -1) at low levels were found mostly in close proximity to reflectivity maxima (45-51 dBZ), which is consistent with findings from North America, that gravitational loading by the precipitation plays a key role in the initiation and maintenance of downdraughts. -from Authors
Keywords: Doppler radar; thunderstorm; wind field; South Africa